Naringenin Enhances the Anti-Tumor Effect of Doxorubicin on HeLa Cervical Cancer Cells Through Cytotoxic Activity and Apoptosis Induction - Larasati, .; Kusharyanti, Indri; Hermawan, Adam; Susidarti, Ratna Asmah; Meiyanto, Edy (Indonesian Journal of Cancer Chemoprevention, 2011)
Naringenin, an abundant flavanon in the peel of citrus fruits is reported to possess anti-proliferative  effect  in  many  cancer  cells.  Herein,  we  investigated  the  cytotoxic  effect  and apoptosis  induction  of  naringenin  in  combination  with  doxorubicin  on  HeLa  cells.  The cytotoxicity assay of naringenin, doxorubicin, and their combination were carried out by using MTT  assay.  Cell  viability  was  used  as  the  parameters  to  evaluate  combination  effectiveness. Cell  cycle  distribution  was  determined  by  flow  cytometry  and  analyzed  using  ModFit  LT  3.0 program.  Apoptosic  assay  was  done  by  double  staining  method  using  Ethidium  Bromide-Acridine  Orange.  Investigation  on  the  expression  of  Bax  and  Bcl-2  were  determined  by immunocytochemistry method. Naringenin and doxorubicin showed cytotoxic effect  on HeLa cells  with  their  IC50  values  of  195  µM  and  1  µM,  respectively.  Whereas  combination  of naringenin  -  doxorubicin  showed  greater  cytotoxicity  compared  the  single  treatment  of doxorubicin.  The  strongest  cytotoxic  activity  was  observed  at  a  combination  of  100  µM naringenin  and  0,5  µM  doxorubicin.  Single  treatment  of  0,5  µM  doxorubicin  for  24  hours  on HeLa cells induced  S-phase arrest while 100 µM naringenin did not affect on HeLa cell cycle. The  combination  induced  S-phase  arrest  with  the  increased  of  sub-G1  phase  percentage.  In accordance with the flow cytometry results, the double staining apoptosis assay results showed the increase of apoptotic cells. Naringenin, doxorubicin, and their combination also increased the  expression  of  Bax  and  decreased  the  expression  of  Bcl-2.  These  results  concluded  that naringenin was a potential co-chemotherapy agent for cervical cancer due to its synergism with doxorubicin.Keywords:  co-chemotherapy,  naringenin,  doxorubicin,  HeLa  cells,  cytotoxicity,  cell  cycle, apoptosis